Surfactant-assisted synthesis of titanium nanoMOFs for thin film fabrication. Issue 72 (19th August 2021) - Romero-Angel, María; Castells-Gil, Javier; Rubio-Giménez, Víctor; Ameloot, Rob; Tatay, Sergio; Martí-Gastaldo, Carlos
Abstract : Dodecanoic acid provides good control on the synthesis of titanium MOF nanoparticles for straightforward fabrication of crystalline, porous thin films. Abstract : We use dodecanoic acid as a modulator to yield titanium MOF nanoparticles with good control of size and colloid stability and minimum impact to the properties of the framework to enable direct fabrication of crystalline, porous thin films.